Planck intermediate results: LIII. detection of velocity dispersion from the kinetic Sunyaev-Zeldovich effect - Aghanim, Nabila; Pettorino, Valeria (Astronomy and astrophysics, 2018)
Using the Planck full-mission data, we present a detection of the temperature (and therefore velocity) dispersion due to the kinetic Sunyaev-Zeldovich (kSZ) effect from clusters of galaxies. To suppress the primary CMB and instrumental noise we derive a matched filter and then convolve it with the Planck foreground-cleaned “2D-ILC” maps. By using the Meta Catalogue of X-ray detected Clusters of galaxies (MCXC), we determine the normalized rms dispersion of the temperature fluctuations at the positions of clusters, finding that this shows excess variance compared with the noise expectation. We then build an unbiased statistical estimator of the signal, determining that the normalized mean temperature dispersion of 1526 clusters is 〈(ΔT/T)2 〉 = (1.64 ± 0.48) × 10−11. However, comparison with analytic calculations and simulations suggest that around 0.7 σ of this result is due to cluster lensing rather than the kSZ effect. By correcting this, the temperature dispersion is measured to be 〈(ΔT/T)2〉 = (1.35 ± 0.48) × 10−11, which gives a detection at the 2.8 σ level. We further convert uniform-weight temperature dispersion into a measurement of the line-of-sight velocity dispersion, by using estimates of the optical depth of each cluster (which introduces additional uncertainty into the estimate). We find that the velocity dispersion is 〈υ2〉 = (123 000 ± 71 000) (km s−1)2, which is consistent with findings from other large-scale structure studies, and provides direct evidence of statistical homogeneity on scales of 600 h−1 Mpc. Our study shows the promise of using cross-correlations of the kSZ effect with large-scale structure in order to constrain the growth of structure.